Ochratoxin A is not detectable in renal and testicular tumours - Fahmy, Nader; Woo, Mark; Alameldin, Mona; MacDonald, Kyle; Goneau, Lee W.; Cadieux, Peter; Pautler, Stephen E. (Canadian Urological Association Journal, 2014)
Introduction: Ochratoxin-A (OTA) is one of the most abundant food-contaminating mycotoxins, known for its nephrotoxicity, neurotoxicity, gonadotoxicity, teratogenicity, immunosuppression and carcinogenesis. OTA has been linked to several genitourinary pathologies, including Balkan nephropathy and genitourinary malignancies. We examine OTA levels in serum samples and tumour specimens collected from patients with renal and testicular tumours. Methods: Frozen samples were obtained from the Ontario Tumour Bank. Serum specimens, along with renal and testicular tumour biopsies, were included in this study. Normal tissue from the negative surgical margins of each tumour served as a control. OTA levels in serum was measured using the enzyme-linked immunosorbent assay (ELISA), while OTA detection in tissue specimens was determined using immunohistochemistry (IHC). Results: We included specimens collected from 56 patients (36 men and 20 women). Histopathology of the 52 renal tumours included 31 (60%) conventional type renal cell carcinomas (RCC),5 (10%) chromophobe RCC, 5 (10%) papillary RCC, 1 (2%) oncocytoma and 10 (19%) upper tract urothelial carcinoma (UC). The 4 testicular tumours included 1 seminomatous (25%) germ cell tumour and 3 (75%) non-seminomatous germ cell tumours. OTA was detected in the serum of renal tumour patients, with a range from 0.004 to 0.25 ng/mL (mean: 0.07 and median 0.06 ng/mL).There was no OTA signal detected by IHC staining in all testedrenal and testicular tumours. Conclusions: The OTA levels detected in the serum of patients were highly variable and relatively low. No OTA was detected in the tissue samples.